Analysis of 3D linear elastic masonry-like structures through the API of a finite element software. (July 2019) - Briccola, Deborah; Bruggi, Matteo
Highlights: 3D no-tension masonry-like structures are analysed using an energy-based approach. The solving algorithm iteratively calls a finite element software for orthotropic solids. A limited number of iterations is needed to solve the equilibrium for any compatible load. Load paths are shown in cracked solids of general shapes, such as masonry vaults and domes. The collapse load multiplier is computed with no a priori assumption on the mechanism. Abstract: A new numerical procedure is presented to perform the analysis of three-dimensional linear elastic no-tension structures exploiting the application programming interface of a general purpose finite element analysis software. Masonry is replaced by an equivalent orthotropic material with spatially varying elastic properties and negligible stiffness in the case of cracking strain. A non-incremental algorithm is implemented to define the distribution of the equivalent material, minimizing the strain energy so as to achieve a compression-only state of stress for any given compatible load. Applications are shown for masonry-like solids of general shape visualizing load paths in walls subject to dead loads and out-of-plane live loads, circular domes under self-weight and a groin vault acted upon by both vertical and horizontal seismic loading.